Adubação com potássio nas características agronômicas e na qualidade de sementes de soja - Ferreira, Valquíria de Fátima (2015)
The availability of nutrients for plants producing seeds may influence the production and quality, different responses and effects of potassium fertilization in the development of the culture were found. Thus, this study aimed to determine the effects of potassium fertilization in the groove, thrown on top of the soil, onto soil cover in the soybean crop establishment and its consequence in the production process and seed quality. To conduct the study, four soybean cultivars of Syngenta were used, 1379 IPRO SYN, SYN 1263 RR, SYN 1279 RR and a noncommercial cultivar (NC IPRO). It was conducted two trials, one in greenhouse in Lavras - MG, and the other one in a field in Lucas do Rio Verde - MT. Different types of potassium fertilization were used under greenhouse conditions: 1 - Recommended dosage in the groove, 2 - Twice the recommended dosage in the groove, 3 - Recommended dosage for fertilizer thrown on top of soil 4 - Recommended dosage for coverage, 5 – Control without potassium fertilizer. In the experiment in the field beyond the fertilization done in the greenhouse was also used the double of the dose thrown on top of the soil and the double of recommended dose for potassium in coverage. The study in greenhouse was conducted in a completely randomized design in a factorial 4x5 (cultivars x potassium fertilization methods) with three replications. In the field the factorial design was randomized blocks in a factorial 4x7 (cultivars x potassium fertilization methods) with 4 replications. Evaluations of plant height, first legume insertion, number of pods/ plant, dry matter of root and shoot and productivity were carried out. To evaluate the physiological quality of seeds the following tests were performed: first count of germination, germination, emergency, emergency speed index, electrical conductivity and potassium leaching (only greenhouse). The influence of potassium fertilization on physiological quality of soybean seeds and the agronomic characteristics of the plants varies according to genotype. The use of potassium fertilizer thrown on top of the soil considering the recommended dose or double the dosage provides greater rooting and plant height in the field, greatest yields for these treatments were also observed. The malate dehydrogenase enzyme, alcohol dehydrogenase and esterase were efficient to detect differences in the use of potassium fertilization in soybean seeds. Potassium fertilization does not affect the physiological quality of soybean seeds during storage. The sanitary quality of soybean seeds is directly related to genotype and potassium fertilization does not interfere in it.